The University's Reputation as Intervening Is Between Quality of Service and Electronic Word of Mouth at Private Universities in Medan City - Mesra B; Arlina Nurbaity Lubis; Endang Sulistya Rini; Amlys Syahputra Silalahi (AIBPM Publisher, 2021)
This study aims to see the direct influence of service quality rather than electronic word of mouth (EWOM) and by presenting the role of the university's reputation in mediating the quality of service at EWOM at private universities in Medan City. A sampling of 120 respondents from five private universities with active student status, a minimum study period of three semesters, and a strata 1 education level. The research methodology used is path analysis with the Smart PLS Program Version 3. The results show that the service quality is directly greater. its effect on EWOM when compared to the effect from service quality on EWOM is mediated by the reputation of the university at private universities in Medan City.